ALTERNATIF PENGGUNAAN MULTIMEDIA KONTEKSTUAL PADA MATERI EKOSISTEM DENGAN MODEL PEMBELAJARAN BERDASARKAN MASALAH (PBM) - Vica Dian Aprelia Resti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
A good learning depends on the curriculum representative. Curriculum representative is realized by using facilities and subject matter to get competency. The purpose of curriculum 2013 at Junior High School is expected that students have factual knowledge, conceptual, prosedural and related whith real problem, so it is able to interact with the social and natural environment, to act effectively and creatively in the realm of the abstract and concrete. In this case the background of paper is describing the alternative by using contextual multimedia at Ecosystem matter on the Problem Based Learning (PBL) model. PBL as the model includes all developing curriculum or sets developing that presenting an real and meaningful problems to make their students conduct investigations. It is relevance with Ecosystem matter emphasize the real problems in the environments. Learning activities which student are able to understand the problems, will have critical thinking about a phenomenon in environments.The use of multimedia is one of alternative to orient on real problem with more efficient when direct observation is not able to be implemented. Educators want to be responsive and creative which presenting any problem to make their students get critical thinking. Some suggestions to educator in order that they are able to present real problem with observation or with multimedia. The use of technology as learning media must be based on the requirement and it can not separated with the role of educator as fasilitators. Keywords: contextual multimedia, ecosystem, PBL model